COMMUNITY EMPOWERMENT THROUGH THE PROCESSING OF LIBUAI SOAP (ANTI-IRRITATION ALOE VERA) IN KAMPUNG MATANG TEUPAH - Marjanah; Nurhafidhah; Hartutik Hartutik (LPPM dan PM Universitas Samudra, 2021)
Bendahara sub-district, to be precise, Teupah mature village is a location that is the target place for the community service eam to make a product that is beneficial to the community. As we know that in a mature village, the majority of the population are farmers. So that the business opportunity that we provide to the community is to make Libuai Soap (Anti-Irritation Aloe Vera) products. The Libuai bath soap making training targets the local community, especially mothers and young women. This soap is used to clean the skin from dirt, dust, and bacteria that stick to the skin. The objectives of community service activities are: (1) providing training to the local community on how to make anti-irritant aloe vera soap products that are not yet known to the wider community; (2) providing knowledge to the public regarding the prospects and competitiveness of anti-irritant aloe vera soap products compared to other soaps; (3) provide knowledge to the public about the methods that can be used to market anti-irritant aloe vera soap products. Implementation methods in community service activities are planning, process, marketing and evaluation. The results of this activity are in accordance with the predetermined plan and the activities run well and smoothly starting from the planning, marketing, and evaluation processes. It is hoped that with the implementation of this activity the local community can process their own soap with other variations so that they can foster entrepreneurial opportunities.